An Application of Machine Learning Algorithms by Synergetic Use of SAR and Optical Data for Monitoring Historic Clusters in Cypriot Cities - Tzima, Maria Spyridoula; Agapiou, Athos; Lysandrou, Vasiliki; Artopoulos, Georgios; Fokaides, Paris; Chrysostomou, Charalambos (My University, 2023)
In an era of rapid technological improvements, state-of-the-art methodologies and tools dedicated to protecting and promoting our cultural heritage should be developed and extensively employed in the contemporary built environment and lifestyle. At the same time, sustainability principles underline the importance of the continuous use of historic or vernacular buildings as part of the building stock of our society. Adopting a holistic, integrated, multi-disciplinary strategy can link technological innovation with the conservation and restoration of heritage buildings. This paper presents the ongoing research and results of the application of Machine Learning methods for the remote monitoring of the built environment of the historic cluster in Cypriot cities. This study is part of an integrated, multi-scale, and multi-disciplinary study of heritage buildings, with the end goal of creating an online HBIM platform for urban monitoring.
Keywords: change detection; historic architecture clusters; land cover classification; machine learning; remote sensing; Sentinel-1; Sentinel-2; SNAP; urban heritage